Is diagnostics of Benign Paroxysmal Positional Vertigo with a mechanical rotation chair superior to traditional manual diagnostics? A randomized controlled crossover study - Hentze, Malene; Hougaard, Dan Dupont; Kingma, Herman (Frontiers in Neurology, 2024)
BackgroundBenign Paroxysmal Positional Vertigo (BPPV) is the most common cause of vertigo. While various techniques and technologies have improved BPPV diagnostics and treatment, optimizing BPPV healthcare pathways requires a comprehensive understanding of the diagnostic modalities across diverse clinical settings.ObjectiveTo compare traditional manual BPPV diagnostics (MD) with diagnostics done with the aid of a mechanical rotation chair (MRC) when using videonystagmography goggles with both modalities.MethodsThis prospective, open-label, randomized diagnostic crossover study involved 215 adults with typical BPPV symptoms at a tertiary University Hospital-based outpatient clinic (Aalborg University Hospital, Denmark). Participants referred by general practitioners or otorhinolaryngologist clinics underwent both traditional manual and MRC diagnostics with the aid of videonystagmography goggles. The order of the diagnostic modalities was randomly assigned, and the two modalities were separated by a minimum of 30 min. The primary outcomes included sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of traditional MD compared to MRC diagnostics. The secondary outcome was the agreement between the two modalities.ResultsThe MRC demonstrated a significantly higher sensitivity for BPPV detection in general for all participants (p = 0.00). Compared to MRC diagnostics, traditional MD displayed a sensitivity of 69.5% (95% confidence interval (CI): 59.8–78.1), specificity of 90.9% (95% CI: 83.9–95.6), PPV of 88.0% (95% CI: 83.9–95.6), and NPV of 75.8% (95% CI: 67.5–82.8). The overall inter-modality agreement was 80.5% (95% CI: 75.2–85.8, Cohen’s kappa 0.61). While both modalities detected unilateral posterior canal BPPV equally good (p = 0.51), traditional MD underperformed for non-posterior BPPV (significantly) and in subgroups referred by ENTs (trend) or with impaired cooperation during traditional MD (significantly).ConclusionTraditional manual BPPV diagnostics remains a valuable first-line approach for most patients. However, MRC diagnostics offers advantages for complex BPPV cases, patients with impaired cooperation, patients referred from otorhinolaryngologist clinics, and those with negative traditional MD but an evident BPPV history. MRC may be useful as a second opinion diagnostic tool for treatment-resistant BPPV.Clinical trial registrationClinicalTrials.gov identifier: NCT05846711.